The gift economy - Lichtblau, Klaus (Universidade Estadual Paulista / UNESP, 2018)
Starting with Marcel Mauss's classical arguments suggesting the existence of a fundamental aporia in the concept of the gift, this article discusses under what conditions one can consistently speak of a “gift economy.” This question is initially addressed by means of an examination of the linguistic and social origins of the notions of “the economy” and “the gift.” Following the arguments of Claude Lévi-Strauss, Pierre Bourdieu, Jean Baudrillard, Aldo Haesler and Alain Caillé, the article then proposes to conceive the gift as a crucial element of the symbolic exchange, based on an interest in the maintenance of social bonds as an “end in itself.” Finally, contemporary forms of gift relations and of potlatch are analyzed and criticized.